Development Support Communication in Practice: Towards Realizing Child Rights Through UNICEF. (December 2019) - Brody, Alan
The author studied 6 years with Professor Joe Ascroft at the University of Iowa on a team defining principles of Development Support Communication (DSC, now widely called C4D). In 1984, he returned to the world of development practice and a 22-year career with UNICEF. The article describes his first assignment in Nigeria using an innovative communication strategy to speed the adoption of oral rehydration therapy for treatment of diarrhoea and dehydration. It also summarizes subsequent work that applied perspectives and expertise in communication to UNICEF's challenges to further child rights: involving pharmacists as promoters of oral rehydration, and helping to launch the global 'Baby Friendly Hospital Initiative' in Turkey; formulating a strategy to apply national mass campaign approaches pioneered in global vaccination initiatives to reduce pneumonia deaths in Central Asia; working on emergency programmes in the 'failed state' of Afghanistan; building support and understanding of child rights in China, along with strengthening decentralized capacities to monitor progress towards World Summit for Children goals and targets; and as UNICEF Representative in Swaziland tackling challenges of one of the world's worst HIV and AIDS crises. He provides seven key ideas and principles—drawn from 'DSC Iowa Style'—that guided his development work over those years.